2014
DOI: 10.1080/02660830.2014.11661659
|View full text |Cite
|
Sign up to set email alerts
|

Positioning further education and community colleges: Text, teachers and students as global discourse

Abstract: This paper explores ideas about quality in further education and community colleges as articulated by two policy texts. Published in 2012 'How Colleges improve' examines the factors that have contributed towards sustained high performance or improvement in Further Education (FE) colleges in the UK. 'The Heart of Student Success: teaching, learning and college completion' published in 2010, focuses on similar set of concerns for Community College (CC) students in the US. Both documents are analysed as enactment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Therefore, the University of Mobile's technology of the future requires a vast array of capabilities in computer, communications, and mobile information technology of all kinds [29]. [36] It was concluded that colleges in the future must prioritize quality in all aspects of the educational process to generate high-quality educational outcomes that play a significant role in serving society.…”
Section: Technological Forecastingmentioning
confidence: 99%
“…Therefore, the University of Mobile's technology of the future requires a vast array of capabilities in computer, communications, and mobile information technology of all kinds [29]. [36] It was concluded that colleges in the future must prioritize quality in all aspects of the educational process to generate high-quality educational outcomes that play a significant role in serving society.…”
Section: Technological Forecastingmentioning
confidence: 99%